DbpA: a DEAD box protein specifically activated by 23s rRNA. - Fuller-Pace, F V (1993)
The Escherichia coli protein DbpA is a member of the 'DEAD box' family of putative RNA-dependent ATPases and RNA helicases, so called because they share the highly conserved motif Asp-Glu-Ala-Asp, together with several other conserved elements. We have investigated DbpA expression under conditions where an endogenous promoter is used. In this context, translation initiation does not occur at the previously identified AUG, but at an upstream, in-frame GUG. Mutation of the GUG initiation codon to AUG virtually abolishes DbpA expression, suggesting an unusual translation initiation mechanism. Using an inducible overexpression plasmid, we have purified milligram quantities of DbpA to homogeneity and shown that the purified protein hydrolyses ATP in an RNA-dependent manner. This ATPase activity is interesting in that, unlike that of other DEAD box proteins investigated to date, it absolutely requires a specific bacterial RNA, which we have identified as 23S rRNA. This observation is particularly significant since DbpA will bind other RNAs and DNA, but will only hydrolyse ATP in the presence of 23S rRNA.